Regio‐ and Enantioselective Synthesis of Sulfone‐Bearing Quaternary Carbon Stereocenters by Pd‐Catalyzed Allylic Substitution - Khan, Ajmal; Zhao, Heng; Zhang, Meina; Khan, Shahid; Zhao, Depeng (Angewandte Chemie International Edition, 2020)
Chiral sulfones are of great importance in medicinal chemistry and chemical synthesis. Efficient methods for preparing enantiomerically enriched sulfone‐containing molecules can therefore be of significant value; such methods, however, are uncommon. Herein, we report the first general palladium‐catalyzed sulfonylation of vinyl cyclic carbonates with sodium sulfinates. A series of enantiomerically enriched tertiary allylic sulfones were synthesized in good yields with excellent enantiomeric ratios. Both aliphatic‐ and aryl‐substituted vinyl cyclic carbonates are suitable reactants with excellent results. This reaction features broad substrates scope, readily available starting materials, excellent regio‐ and enantioselectivity, and synthesis of sulfone‐bearing quaternary carbon stereocenters. Through the sulfonylation of geranyl derived cyclic carbonate 1 h, we achieve the formal total synthesis of (+)‐agelasidine A. The first general example of regio‐ and enantioselective palladium catalyzed allylic sulfonylation of vinyl cyclic carbonates provides an efficient and direct way to construct sulfone‐bearing quaternary carbon stereocenters. A three steps formal total synthesis of (+)‐agelasidine A is achieved which exemplifies the practical use of this protocol in a synthetic setting.